Efeitos do treinamento intervalado associado ao extrato aquoso de Uncaria Tomentosa sobre os biomarcadores de estresse oxidativo e danos musculares em ratos sem e com lesão nervosa periférica - Santos, Alisson dos (2024)
Introduction: High-Intensity Interval Training (HIIT) can induce oxidative stress in both healthy animals and those with peripheral nerve injury. However, supplementation with antioxidant plant extracts, such as Uncaria tomentosa (cat's claw), may mitigate this stress. Therefore, Uncaria tomentosa stands out as a promising strategy to protect against oxidative damage caused by HIIT, both under normal conditions and in the presence of injuries.Objective: To assess the effects of HIIT combined with aqueous extract supplementation of Uncaria tomentosa on oxidative stress biomarkers and tissue damage in Wistar rats with and without peripheral nerve injury. Methods: Following the guidelines of the Graduate Program in Physical Education/UFS, a "B" dissertation model was chosen, consisting of three studies. Studies 1 and 2 have been accepted for publication in journals, while Study 3 is currently under submission. Results: Study 1: Provided a brief update on the physiological effects of HIIT, highlighting benefits such as improved mitochondrial function, increased muscle capillary density, and enhanced antioxidant capacity. HIIT also promotes greater calorie burning during and after exercise, contributing to weight loss and reduced body fat.Study 2: Aimed to evaluate the effect of four weeks of high-intensity interval training on a treadmill combined with supplementation of aqueous Uncaria tomentosa extract on oxidative stress markers and tissue damage in healthy rats. Sedentary control animals (CT, n=10) aged 3 months and sedentary animals supplemented with 200 mg/kg of Uncaria tomentosa extract (CS, n=10) for 4 weeks, along with trained animals undergoing 4 weeks of HIIT on a treadmill (TR, n=10) and trained animals supplemented with 200 mg/kg of Uncaria tomentosa extract (TS, n=10), had their blood and muscle tissues collected at the end of the intervention for analysis of tissue damage and oxidative stress markers. The intervention resulted in significant responses in oxidative damage markers: CK (F=31.98), LDH (F=117.95), ALT (F=5.34, p=0.0005), and AST (F=28.34, p<0.001). The SH variable in tissues—Triceps (44.34%), Soleus (136.65%), Gastrocnemius (81.14%), and Quadriceps (21.06%)—increased compared to the TR group, while MDA levels in the Soleus (80.15%), Gastrocnemius (80.17%), and Quadriceps (28.00%) decreased relative to the TR group. Study 3: Aimed to investigate the effects of combining high-intensity interval training on a treadmill with the intake of Uncaria tomentosa aqueous extract on oxidative stress markers and muscle damage in young adult Wistar rats with peripheral nerve injury. The animals subjected to surgical procedures without nerve injury (GSHAM, n=10) aged 3 months, and animals with nerve injury receiving 200 mg/kg of Uncaria tomentosa extract (GLE, n=10) for 4 weeks, along with injured animals undergoing HIIT on a treadmill for 4 weeks (GTL, n=10), and injured animals that were both trained and supplemented with 200 mg/kg of Uncaria tomentosa extract (GTLE, n=10), had their blood and muscle tissues collected at the end of the intervention for analysis of tissue damage and oxidative stress markers. The GTLE group showed a 25.76% reduction in serum CK levels compared to the GTL group. There was an increase in total sulfhydryl levels in the quadriceps muscle of the GLE, GTL, and GTLE groups, by 62.92%, 98.40%, and 157.06%, respectively, compared to the GSHAM group. Conclusion: All three studies concluded that HIIT significantly improves antioxidant capacity. Furthermore, Uncaria tomentosa can reduce muscle damage and oxidative stress after HIIT, enhancing adaptive effects and improving the antioxidant system, with positive results in muscle recovery and performance.